Electrophoretic deposition of Ba0.5Sr0.5Co0.8Fe0.2O3−∞SDC carbonate composite coating on solid oxide fuel cell interconnect - Tan, K. H.; Rahman, H. A.; Taib, H.; Sazali, M. F. (Microscopy Society of Malaysia (MSM), 2018)
Application of protective coating on ferritic stainless steel (FSS) as interconnect is crucially essential to restrict degradation of cell performance. In this study, barium strontium cobalt ferrite-samarium doped ceria (Ba0.5Sr0.5Co0.8Fe0.2O3−δ-Sm0.2Ce0.8O1.9) carbonate (BSCF-SDCC) composite perovskite powder are fabricated by low speed wet milling method. The BSCF-SDCC is then applied as protective coating on ferritic stainless steel via electrophoretic deposition (EPD) technique. The BSCF-SDCC perovskite powder is examined by X-ray diffraction (XRD) and elemental energy dispersive X-ray spectroscopy (EDS). The characterisation of deposition is examined by scanning electron microscope (SEM). XRD displayed distinct crystalline phases of BSCF and SDCC and EDX results displayed a uniform element distribution in powder after milling. The EPD of BSCF-SDCC perovskite powder on ferritic stainless steel is conducted at 5 V to 12 V with duration of coating from 5 min to 20 min in an organic solvent. EPD at 10V for 10 min and 12V for 5min are found to produce the best coating parameter through the observation of the deposition morphology and thickness. Crack free and uniform coating are observed. The highest deposition weight and thickness obtained is 7.2mg and 81.6µm respectively. Hence EPD method has been successfully applied in depositing perovskite BSCF-SDCC on stainless steel with remarkable coating properties.